2016
DOI: 10.1292/jvms.16-0367
|View full text |Cite
|
Sign up to set email alerts
|

Genetic subtyping of <i>Listeria monocytogenes</i> via multiple-locus sequence typing using <i>iap, sigB</i> and <i>actA</i>

Abstract: Pulse field gel electrophoresis (PFGE) is widely used for listeriosis surveillance. Although this technique is effective for epidemiology, the data among laboratories are inconsistent. We previously reported a method for Listeria monocytogenes subtyping combined with sequence analysis of partial iap and whole genome restriction fragment length polymorphism (RFLP) using XbaI, ClaI (BanIII) and PstI. However, distinguishing subtypes was challenging, because the output comprised complicated fragment patterns. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…On the basis of the data, both phylogenic trees were divided into two large clades, representing lineage I ( and traditional MLST genes. In a previous study, we reported that two strains, 76P1 (Table 3) and 1E1 (sigB AT 37; derived from the skin of beef cattle), possessed nonsense mutations in the sigB gene (6). According to genetic analysis of the sigB allele, this sequence was found to be relatively conserved in L. monocytogenes (14).…”
mentioning
confidence: 96%
“…On the basis of the data, both phylogenic trees were divided into two large clades, representing lineage I ( and traditional MLST genes. In a previous study, we reported that two strains, 76P1 (Table 3) and 1E1 (sigB AT 37; derived from the skin of beef cattle), possessed nonsense mutations in the sigB gene (6). According to genetic analysis of the sigB allele, this sequence was found to be relatively conserved in L. monocytogenes (14).…”
mentioning
confidence: 96%